Mass spectrometry of rhenium complexes: a comparative study by using LDI‐MS, MALDI‐MS, PESI‐MS and ESI‐MS - Petroselli, Gabriela (2012)
A group of rhenium (I) complexes including in their structure ligands such as CF3SO3-, CH3CO2-, CO, 2,2′-bipyridine, dipyridil [3,2-a:2′3′-c]phenazine, naphthalene-2-carboxylate, anthracene-9-carboxylate, pyrene-1-carboxylate and 1,10-phenanthroline have been studied for the first time by mass spectrometry. The probe electrospray ionization (PESI) is a technique based on electrospray ionization (ESI) that generates electrospray from the tip of a solid metal needle. In this work, mass spectra for organometallic complexes obtained by PESI were compared with those obtained by classical ESI and high flow rate electrospray ionization assisted by corona discharge (HF-ESI-CD), an ideal method to avoid decomposition of the complexes and to induce their oxidation to yield intact molecular cation radicals in gas state [M]+. and to produce their reduction yielding the gas species [M]–. . It was found that both techniques showed in general the intact molecular ions of the organometallics studied and provided additional structure characteristic diagnostic fragments. As the rhenium complexes studied in the present work showed strong absorption in the UV–visible region, particularly at 355 nm, laser desorption ionization (LDI) mass spectrometry experiments could be conducted. Although intact molecular ions could be detected in a few cases, LDI mass spectra showed diagnostic fragments for characterization of the complexes structure. Furthermore, matrix-assisted laser desorption ionization (MALDI) mass spectra were obtained. Nor-harmane, a compound with basic character, was used as matrix, and the intact molecular ions were detected in two examples, in negative ion mode as the [M]–. species. Results obtained with 2-[(2E)-3-(4-tert-buthylphenyl)- 2-methylprop-2-enylidene] malononitrile (DCTB) as matrix are also described. LDI experiments provided more information about the rhenium complex structures than did the MALDI ones.